The Successful Anesthetic Management of a Cesarean Delivery in a Patient with Fanconi–Bickel Syndrome - Alexander M. DeLeon; Rishi D. Gaiha; Feyce M. Peralta (Case Reports in Anesthesiology)
Introduction. Fanconi–Bickel syndrome (FBS) is a rare genetic condition characterized by extremely short stature, renal tubular dysfunction, osteoporosis, and rickets. The literature is scant regarding the successful reproduction of women with FBS. Cesarean delivery is indicated due to the risk of pelvic fracture from vaginal delivery in a patient with FBS and rickets, yet no case describing the anesthetic has been reported. Clinical Findings. We present a 39-inch-tall, 46.47 kg/m2 BMI woman with FBS who was scheduled for cesarean delivery and requesting neuraxial anesthesia. A low-dose, combined spinal-epidural technique (CSE) was employed to account for her extreme short stature yet allow for additional dosing if needed. The cesarean delivery, hospital course, and follow-up were all uneventful. Conclusion. A single case of an FBS patient’s successful pregnancy was previously reported in the literature without describing the anesthetic technique. Our case is unique in that it is the first case in the literature that we are aware of describing the anesthetic technique. This case may provide a template for clinicians treating FBS patients and patients with extremely short stature.